Bridging the data gap: using remote sensing and open-access data for assessing sustainable groundwater use in Kumasi, Ghana - Estela Fernandes Potter; Isaac Monney; Martine Rutten (Journal of Water and Climate Change, 2023)
Groundwater use has significantly increased in the rapidly urbanising city of Kumasi, Ghana. But there is a lack of understanding of whether the groundwater system can sustain the growing demand in the future amidst climate change and rapid urbanisation. Using remote sensing datasets and a water balance approach, this study estimated the groundwater recharge and assessed how urbanisation has affected its groundwater sustainability. Sustainability is investigated by comparing multi-annual groundwater withdrawals to long-term average annual replenishment. Results show that while groundwater recharge has decreased by 80% from 1986 to 2020, mainly due to substantial (63%) loss of permeable land, groundwater consumption has seen a six-fold increase. Groundwater consumption in 2020 exceeded the long-term average groundwater recharge by 2.2Mm3, suggesting that the current groundwater use trends are unsustainable for future groundwater availability. Under a ‘business-as-usual’ scenario, a four-fold increase in groundwater consumption is predicted by 2050 while climate change and land-cover changes may reduce groundwater recharge by 10% and 55% respectively. Practical measures such as promoting artificial groundwater replenishment approaches, adopting low-impact development and instituting demand management measures must be implemented in the Metropolis. This should be informed by further studies to ascertain the exact condition of the groundwater. HIGHLIGHTS Since 1986, groundwater use in Ghana’s fastest-growing city, Kumasi, has increased by six-fold while recharge has dwindled by 8%.; By mid-century, groundwater use can see a four-fold increase while climate change and land cover changes may reduce groundwater recharge by 10 and 55%, respectively.; Promoting artificial groundwater recharge approaches in the Metropolis is key to ensuring the availability of groundwater for future generations.;